2005
DOI: 10.1021/bi047848a
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Lumazine Synthase from Mycobacterium tuberculosis as a Target for Rational Drug Design:  Binding Mode of a New Class of Purinetrione Inhibitors,

Abstract: The enzymes involved in the biosynthesis of riboflavin represent attractive targets for the development of drugs against bacterial pathogens, because the inhibitors of these enzymes are not likely to interfere with enzymes of the mammalian metabolism. Lumazine synthase catalyzes the penultimate step in the riboflavin biosynthesis pathway. A number of substituted purinetrione compounds represent a new class of highly specific inhibitors of lumazine synthase from Mycobacterium tuberculosis. To develop potent ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
81
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 32 publications
10
81
0
Order By: Relevance
“…The energy minimization procedure turned the indole ring of Trp-27 to a parallel conformation with respect to the plane of the aromatic groups of all inhibitors, whereas the indole group in the empty structure assumed different conformations in different subunits. This conformational change of the side chain of Trp-27 is in good agreement with the conformations of the aromatic groups of tryptophan or phenylalanine found in the structures of different LSs inhibitor complexes (9,10,12,18,49,52,53). The main-chain contacts, found conserved in all orthologous complexes, remained unchanged in the binding models of all inhibitors.…”
Section: Cals/ts13 Cals/ts44 Cals/gj43 Cals/jc33supporting
confidence: 86%
See 2 more Smart Citations
“…The energy minimization procedure turned the indole ring of Trp-27 to a parallel conformation with respect to the plane of the aromatic groups of all inhibitors, whereas the indole group in the empty structure assumed different conformations in different subunits. This conformational change of the side chain of Trp-27 is in good agreement with the conformations of the aromatic groups of tryptophan or phenylalanine found in the structures of different LSs inhibitor complexes (9,10,12,18,49,52,53). The main-chain contacts, found conserved in all orthologous complexes, remained unchanged in the binding models of all inhibitors.…”
Section: Cals/ts13 Cals/ts44 Cals/gj43 Cals/jc33supporting
confidence: 86%
“…(20,21,48). It has been shown that the purinetrione ring system with an attached C5-phosphate side chain resulted in a less potent inhibitor of B. subtilis LS (20); however, it revealed a high inhibition potential for the pentameric enzyme from M. tuberculosis (12,20,49). The present investigation of binding processes has shown that the values of the association constants of those inhibitors to CALS are in a similar range compared with those for M. tuberculosis LS.…”
Section: Cals/ts13 Cals/ts44 Cals/gj43 Cals/jc33mentioning
confidence: 64%
See 1 more Smart Citation
“…Two enzymes involved in the de novo biosynthesis of NAD that affects the NADH/NAD + ratio upon which M. tuberculosis is dependent, have been studied as possible drug targets (Bellinzoni et al, 2002). Genomic analysis studies have suggested that the riboflavin biosynthesis pathway is essential in M. tuberculosis (Morgunova et al, 2005) and the lumazine synthase pathway has been validated as a target for anti-TB drug discovery.…”
Section: Cofactor-related Drug Targetsmentioning
confidence: 99%
“…Figure.1 A schematic diagram of terminal reactions that are catalyzed by lumazine synthase and riboflavin synthase in the pathway of riboflavin biosynthesis. (A) 5-amino-6-ribitylamino-2,4(1H,3H)-pyrimidinedione; (B) 3,4-dihydroxy-2-butanone 4-phosphate; (C) 6,7-dimethyl-8-ribityllumazine; and (D) riboflavin So far various pyrimidine or purine ring containing compounds were reported as potent inhibitors of LS (Persson et al, 1999;Gerhardt et al, 2002;Morgunova et al, 2005;Morgunova et al, 2006;Zhang, Y. et al, 2008;Zhang, X. et al, 2008). These compounds were almost identical to substrate of LS (designated as A in figure1) and inhibit the activity of the enzyme in competitive mechanism.…”
Section: Introductionmentioning
confidence: 99%